2012
DOI: 10.1186/1479-5868-9-111
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the effects of a point-of-purchase nutrition-information intervention in university canteens: a structural equation modelling analysis

Abstract: BackgroundThe importance of canteen meals in the diet of many university students makes the provision of simple point-of-purchase (POP) nutrition information in university canteens a potentially effective way to promote healthier diets in an important group of young adults. However, modifications to environments such as the posting of POP nutrition information in canteens may not cause an immediate change in meal choices and nutrient intakes. The present study aimed at understanding the process by which the PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
2
28
0
1
Order By: Relevance
“…By providing additional information on food, consumers may align their behaviour according to their value‐based interpretation of information, that is, by choosing more healthy food items when nutritional information are provided on restaurant menus (Choi & Zhao, ) or at coffee shops (Costanigro, McCluskey, & Goemans, ). Thereby, a general condition is the understanding of information to consider them in behaviour which has been addressed in different studies on the application of sustainability labels for food products in general and dishes in catering in particular (Grunert, Hieke, & Wills, ; Hoefkens, Pieniak, Van Camp, & Verbeke, ; Pulkkinen, Roininen, Katajajuuri, & Järvinen, ). A second precondition for this alignment has been stated as conformity between personal values and new or additional information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By providing additional information on food, consumers may align their behaviour according to their value‐based interpretation of information, that is, by choosing more healthy food items when nutritional information are provided on restaurant menus (Choi & Zhao, ) or at coffee shops (Costanigro, McCluskey, & Goemans, ). Thereby, a general condition is the understanding of information to consider them in behaviour which has been addressed in different studies on the application of sustainability labels for food products in general and dishes in catering in particular (Grunert, Hieke, & Wills, ; Hoefkens, Pieniak, Van Camp, & Verbeke, ; Pulkkinen, Roininen, Katajajuuri, & Järvinen, ). A second precondition for this alignment has been stated as conformity between personal values and new or additional information.…”
Section: Resultsmentioning
confidence: 99%
“…The ability for information processing as second condition for label influence was specifically addressed by two studies in a university setting where nutrition information in label form were applied. According to these studies, students’ general knowledge on nutrition was positively related to their motivation to comply with nutritional recommendations of a nutritional food label and to change their food choices in the university cafeteria accordingly (Hoefkens, Lachat, Kolsteren, Camp, & Verbeke, ; Hoefkens, Pieniak, et al ). Complementary, the introduction of a keyhole label for modified food options at a worksite canteen which was rated being helpful ‘to figure out whether the canteen food was healthy or not’ significantly decreased the average energy intake per guest without increasing food waste (Lassen et al, , p. 131).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, nutrition information alone is not enough to change food choices and dietary intake. Studies have shown that an even more important moderator than knowledge is personal motivation when changing eating habits, together with interventions that target self-efficacy [95][96][97]. Leading on to the third argument, gamification is not a game as such, but a design process involving motivation.…”
Section: Discussionmentioning
confidence: 99%
“…1 shows, among a total of 235 unduplicated articles identified through keyword and reference searches, 197 were excluded in title and abstract screening. The remaining thirty-eight articles were reviewed in full texts, in which twenty-two studies were excluded due to the following reasons: age ineligibility (n 3) (20)(21)(22) , no assessment of nutrition label use (n 11) (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and an ineligible study design (n 8), which included six experiments that required participants to read a nutrition label (34)(35)(36)(37)(38)(39) , one semi-structured interview (40) and one case-control study (41) . The remaining sixteen articles were included in the review.…”
Section: Resultsmentioning
confidence: 99%